Modified QuEChERS Approach for Analysis of Synthetic Food Dyes in Jellies and Smarties - Adam, Martin; Bajer, Tomáš; Bajerová, Petra; Ventura, Karel (Springer, 2018)
This work deals with the application of the QuEChERS method for extraction of synthetic food dyes (SFD) from confectionery samples: tartrazine (E102), quinoline yellow (E104), cochineal red A (E124), allura red (E129), patent blue V (E131), and brilliant blue (E133). Extraction conditions, like extraction solvent and its amount, sample amount, the pH adjustment and addition of salt, were optimised. The 5 mL of sample, 2 mL of propan-1-ol as extraction solvent with addition of 0.6 g NaCl, 2.4 g MgSO4, and 0.75 mL 35% HCl were experimentally found to be optimal. Analyses of extracts were performed by liquid chromatography with detection of SFD in the visible region. Recoveries of SFD were in the range of 79.3-100.0% with intra-day precision below 4.6% RSD. The modified QuEChERS method connected with liquid chromatography has been applied to quantify SFD in samples of confectionery (smarties and jellies). The whole procedure was evaluated as a fast method for screening of SFD content in samples of jellies and smarties.
Modifikovaný QuEChERS přístup pro analýzu syntetickýh potravinářských barviv v želé a lentilkách
Keywords: QuEChERS; Extraction; Synthetic food dyes; HPLC-Vis; Confectionery; QuEChERS; Extrakce; Syntetická potravinářská barviva; HPLC-Vis; Cukrovinky